2021
DOI: 10.31372/20200504.1114
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Food Insecurity and Depression among Diverse Asian Americans

Abstract: Background: Proper nutrition is an essential component to both physical and emotional health. Food insecurity (FI) is a potentially critical public health problem. The link between FI and elevated risk for depression has been well documented. Yet, it is largely unknown how diverse older adult populations experience FI differently. Therefore, the aims of this study were to examine how gender, race/ethnicity, and nativity may impact the magnitude of the association between FI and depression. Methods: We used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Prior research has demonstrated that experiencing FI over a period of 12 months increases the likelihood of having clinical depression among AAs, but the magnitude of the association between FI and depression can vary across AA subgroups. 30 For example, one prior national study using data from the National Latino and AAs Study National Latino and AAs Study demonstrated that Filipino Americans experienced the highest rates of FI (41%) compared with all other Asians (38%), Chinese Americans (26%), and Vietnamese Americans (26%, 30). However, the association between FI and depression was highest among the Chinese Americans and all other Asian subgroups, and lowest among the Vietnamese and Filipino adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has demonstrated that experiencing FI over a period of 12 months increases the likelihood of having clinical depression among AAs, but the magnitude of the association between FI and depression can vary across AA subgroups. 30 For example, one prior national study using data from the National Latino and AAs Study National Latino and AAs Study demonstrated that Filipino Americans experienced the highest rates of FI (41%) compared with all other Asians (38%), Chinese Americans (26%), and Vietnamese Americans (26%, 30). However, the association between FI and depression was highest among the Chinese Americans and all other Asian subgroups, and lowest among the Vietnamese and Filipino adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between FI and depression was highest among the Chinese Americans and all other Asian subgroups, and lowest among the Vietnamese and Filipino adults. 30 Again, failure to disaggregate data by AA ethnic group would mask the differences in mental health burdens associated with FI across these AA groups.…”
Section: Discussionmentioning
confidence: 99%
“…Despite association between FI and depression has been well described in the literature, the majority of studies about this relationship have been conducted with specific sub-groups such as low-income individuals, immigrants, people living with HIV, among others (20,35,39) . Results using samples from overall population, like our investigation, are scarcer but also indicate FI as an important determinant for the development of mental health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A study that analysed the association between food insecurity and mental disorders in 149 countries showed that individual-level food insecurity status was associated with poorer mental health (19) . Several other studies have already linked food insecurity status to the risk of mental health disorders in diverse contexts and populations (20)(21)(22) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation